INSTRUCTIONS FOR THE GOOD WRITING OF THE HISTORY IN SPAIN (16TH AND 17TH CENTURIES) - Granduque Jose, Maria Emilia [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2019)
Between the 16th and 17th centuries, historic knowledge is enriched, in Spain, not only with the writing of chronicles that report news pertaining to the New World, but also with the treatises drawn up with the purpose of prescribing rules and guidelines for the promotion of a correct and accurate writing about the past. Bearing in mind that the chronicles do not cease to expose, in their prologues and dedications, advice regarding the proper way to record events, the objective of this article is to analyze these two genres, in order to examine the extent to which they helped to secure a shared knowledge about the writing of history. In other words, taking as starting point chronicles as well as treatises of history, the proposal of this work is to examine how the Spanish scholars of the time wrote about their metier.
Keywords: Writing of history; treatise of history; chronicle; Spain; 16th and 17th centuries